Influence of water absorption on fatigue behavior for chopped and woven-glass-fibers-reinforced PMMA denture - Muslem, Zainab R. (Iraqi Journal of Physics, 2011)
The influence of fiber orientation and water absorption on fatigue crack growth resistance for cold cure acrylic (PMMA) reinforced by chopped and woven -glass-fibers were investigated. A weight of 2 g for chopped fibers and the same weight for woven -glass-fibers (one layer) were used to prepare samples. Some of these samples would storage in dry condition; the others were immersed in water for 15 days. Fatigue test was carried out. The results shows that, for PMMA, the initial bending stress for dry specimen was 3.392 N/cm2 and the number of cycles were 1364, the initial bending stress for wet samples was 4.20 N/cm2, and the number of cycles was 2411. The samples would cut in two pieces because of the cracks would propagated fast during the test. Reinforcement PMMA with different kinds of glass fibers would increase the initial bending stresses for all specimens. The cracks would appear slowly during the test, and the specimens will not separate during the test except the samples which reinforced by Woven-Glass-Fibers